Buried alive! : how 33 miners survived 69 days deep under the Chilean desert - Scott, Elaine, 1940- (Houghton Mifflin Harcourt, 2012)
Describes the 2010 mining accident in San José, Chile, in which thirty-three men became trapped underground for over sixty days, and details the rescue efforts and the worldwide media coverage of the event.